A novel configuration for high power-output and highly efficient vibration energy harvesting. (1st August 2021) - Liu, Mingyi; Mi, Jia; Tai, Wei-Che; Zuo, Lei
Highlights: A new configuration similar to the Maxwell model for better energy harvesting performance. Experimentally demonstrated an 82% power increase over the optimized SDOF system. Experimentally validated efficiency increases from the optimized SDOF's 50–83%. Verified with bench test and demonstrated with a bridge vibration energy harvesting. Abstract: The most commonly used vibration energy harvesting system is the single-degree-of-freedom (SDOF) system. However, the power output of the SDOF system is limited by the mechanical damping ratio and the efficiency is only 50% at the maximal power output. In this paper, we modified the SDOF configuration by adding a spring in series with the energy transducer, which results in a configuration where a parallel energy-harvesting damper and inerter are in series with the spring, similar to the Maxwell model. The parameters of the proposed configuration are analyzed and optimized. The optimization results show the new configuration can produce many times more power output compared with the conventional SDOF system if the primary spring is relatively soft and the added spring is properly selected. In addition, the energy-harvesting efficiency can be significantly increased at the maximal power output. A lab experiment of backpack setup demonstrated 82% power increase and an efficiency of 83%. Lab test using a bridge vibration induced by freight train finds out that the proposed configuration can double the power output compared with the conventional SDOF system. With the augment of a simple spring, the proposed configuration disrupts the fundamental limit on the power and efficiency of the conventional SDOF energy-harvesting system, which opens a new perspective in the energy-harvesting field.